Pickers and Poets : The Ruthlessly Poetic Singer-Songwriters of Texas - Clifford, Craig Edward, 1951-; Hillis, Craig D., 1949- (Book collections on Project MUSE., 2016)
Many books and essays have addressed the broad sweep of Texas music-its multicultural aspects, its wide array and blending of musical genres, its historical transformations, and its love/hate relationship with Nashville and other established music business centers. This book, however, focuses on an essential thread in this tapestry: the Texas singer-songwriters to whom the contributors refer as "ruthlessly poetic." All songs require good lyrics, but for these songwriters, the poetic quality and substance of the lyrics are front and center. Obvious candidates for this category would include Tow.